ANALISIS PENGARUH BAHASA GAUL PADA MEDIA SOSIAL TERHADAP KEMURNIAN BAHASA INDONESIA - Trivena Kezia Silaban; Hesti Herawati Siagian; Ria Agustina Sigiro; Stevani Nababan; Tri Febriani Sipayung (JIP: Jurnal Ilmu Pendidikan, 2024)
This study aims to analyze the influence of slang language on social media on the purity of Indonesian language, focusing on the perspectives of students at Universitas Negeri Medan. Using a descriptive quantitative survey method, the research involved 61 respondents who completed a questionnaire about language habits and perceptions of slang language. Research findings reveal that 93.4% of respondents acknowledge social media's significant role in spreading slang among young generations. As many as 77% agree that slang can dilute the purity of Indonesian language, and 80.3% experience its impact in daily communication. Interestingly, 95.1% of respondents attempt to avoid using slang in formal communication.The study concludes that although slang language has a strong influence, there is a high awareness among students to preserve the integrity of Indonesian language. Respondents recognized that slang can cause confusion and affect understanding, especially in educational contexts. The primary recommendations include strengthening language education, media campaigns, and developing contextual language usage guidelines.The research highlights the dynamic tension between linguistic evolution and language preservation in the digital age, emphasizing the need for balanced and conscious language use among young Indonesian speakers.